Plasma procalcitonin in patients with ileus. Relations to other inflammatory parameters - Maruna, Pavel; Fraško, Roman; Gürlich, Robert (Physiological research, 2008)
Plasma procalcitonin (PCT) is a highly specific marker for the diagnosis of bacterial infections and sepsis. PCT levels are usually low in viral infections, chronic inflammation or postsurgical states. The purpose of this study was to characterize PCT plasma levels in patients with various types of ileus at preoperative stage, where the other inducing factors such as a surgical stress are excluded. The prospective study was performed on 54 patients admitted to in-patient surgical department with a proven diagnosis of ileus. Patients were divided to three groups--obstructive, vascular and paralytic ileus. Plasma levels of PCT (Kryptor analysis), TNFalpha, IL-1beta, IL-6, cortisol (ELISA) and CRP (Kryptor ultrasensitive analysis) were estimated before any invasive procedure was realized. We demonstrated significant elevation of PCT in both obstructive ileus in adhesions and vascular ileus compared with healthy subjects (p 0.01). PCT levels were not elevated in paralytic ileus. The regression coefficient was the highest for PCT and CRP (r=0.78, p 0.01), for TNFalpha and IL-8 (r=0.76, p 0.01) in vascular ileus. There was no significant correlation between PCT and other inflammatory parameters. The different types of ileus induce an elevation of plasma PCT levels and PCT shows itself as an acute phase reactant. The highest PCT concentrations were presented in patients with vascular ileus, whereas paralytic ileus revealed similar cytokine and PCT pattern as in healthy subjects. Plasma PCT estimation extended to a measurement of CRP and IL-6 may become a useful complementary examination for diagnostics of acute abdomen in patients.
Keywords: financování organizované; dospělí; Protein Precursors; Enzyme-Linked Immunosorbent Assay; Female; biologické markery; C-Reactive Protein; Biomarkers; Adult; Tumor Necrosis Factor-alpha; ženské pohlaví; Calcitonin; hydrokortison; lidé; Hydrocortisone; Inflammation Mediators; Intestinal Obstruction; ileus; Interleukin-6; Intestinal Pseudo-Obstruction; proteinové prekurzory; Financing, Organized; TNF-alfa; ELISA; prospektivní studie; Interleukin-1beta; Male; Aged; Prospective Studies; střevní obstrukce; interleukin-6; Ileus; interleukin-1beta; střevní pseudoobstrukce; mediátory zánětu; C-reaktivní protein; lidé středního věku; kalcitonin; senioři; mužské pohlaví; Middle Aged; Humans